Can you solve this problem?

Algebra Level 3

Given that A is the set of the answer(s) of the equation :

5 1 + x 2 4 x 1 + 5 5 + 4 x x 2 2 + x 2 4 x 1 5^{1+\sqrt{x^{2}-4x-1}} + 5^{\frac{5+4x-x^2}{2+\sqrt{x^{2}-4x-1}}} = 126

What is the sum of the element(s) in set A?


The answer is 4.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Ikkyu San
Oct 13, 2015

5 1 + x 2 4 x 1 + 5 5 + 4 x x 2 2 + x 2 4 x 1 = 126 5 1 5 x 2 4 x 1 + 5 5 + 4 x x 2 2 + x 2 4 x 1 2 x 2 4 x 1 2 x 2 4 x 1 = 126 5 5 x 2 4 x 1 + 5 ( 5 + 4 x x 2 ) ( 2 x 2 4 x 1 ) 4 ( x 2 4 x 1 ) = 126 5 5 x 2 4 x 1 + 5 ( 5 + 4 x x 2 ) ( 2 x 2 4 x 1 ) 5 + 4 x x 2 = 126 5 5 x 2 4 x 1 + 5 2 x 2 4 x 1 = 126 5 5 x 2 4 x 1 + 5 2 5 x 2 4 x 1 = 126 \large\begin{aligned}5^{1+\sqrt{x^2-4x-1}}+5^{\frac{5+4x-x^2}{2+\sqrt{x^2-4x-1}}}=&\ 126\\5^1\cdot5^{\sqrt{x^2-4x-1}}+5^{\frac{5+4x-x^2}{2+\sqrt{x^2-4x-1}}\cdot\frac{2-\sqrt{x^2-4x-1}}{2-\sqrt{x^2-4x-1}}}=&\ 126\\5\cdot5^{\sqrt{x^2-4x-1}}+5^{\frac{(5+4x-x^2)(2-\sqrt{x^2-4x-1})}{4-(x^2-4x-1)}}=&\ 126\\5\cdot5^{\sqrt{x^2-4x-1}}+5^{\frac{(5+4x-x^2)(2-\sqrt{x^2-4x-1})}{5+4x-x^2}}=&\ 126\\5\cdot5^{\sqrt{x^2-4x-1}}+5^{2-\sqrt{x^2-4x-1}}=&\ 126\\5\cdot5^{\sqrt{x^2-4x-1}}+\frac{5^2}{5^{\sqrt{x^2-4x-1}}}=&\ 126\end{aligned}

Let a = 5 x 2 4 x 1 \large a=5^{\sqrt{x^2-4x-1}} That is,

5 a + 25 a = 126 5 a 2 + 25 = 126 a 5 a 2 126 a + 25 = 0 ( 5 a 1 ) ( a 25 ) = 0 a = 1 5 , 25 \begin{aligned}5a+\frac{25}a=&\ 126\\5a^2+25=&\ 126a\\5a^2-126a+25=&\ 0\\(5a-1)(a-25)=&\ 0\\a=&\ \frac15,\ 25\end{aligned}

Case ( 1 ) (1) : a = 1 5 a=\frac15 That is,

5 x 2 4 x 1 = 1 5 5 x 2 4 x 1 = 5 1 x 2 4 x 1 = 1 \large\begin{aligned}5^{\sqrt{x^2-4x-1}}=&\ \frac15\\5^{\sqrt{x^2-4x-1}}=&\ 5^{-1}\\\sqrt{x^2-4x-1}=&\ -1\end{aligned}

But x 2 4 x 1 0 \sqrt{x^2-4x-1}\geq0 Thus, this case has no real solution.

Case ( 2 ) (2) : a = 25 a=25 That is,

5 x 2 4 x 1 = 25 5 x 2 4 x 1 = 5 2 x 2 4 x 1 = 2 x 2 4 x 1 = 4 x 2 4 x 5 = 0 ( x + 1 ) ( x 5 ) = 0 x = 1 , 5 \large\begin{aligned}5^{\sqrt{x^2-4x-1}}=&\ 25\\5^{\sqrt{x^2-4x-1}}=&\ 5^2\\\sqrt{x^2-4x-1}=&\ 2\\x^2-4x-1=&\ 4\\x^2-4x-5=&\ 0\\(x+1)(x-5)=&\ 0\\x=&\ -1,5\end{aligned}

Hence, A = { 1 , 5 } A=\{-1,5\} and the sum of the elements in set A A is 1 + 5 = 4 -1+5=\boxed4

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...